2019
DOI: 10.1590/1678-4685-gmb-2017-0293
|View full text |Cite
|
Sign up to set email alerts
|

Cross-genera SSR transferability in cacti revealed by a case study using Cereus (Cereeae, Cactaceae)

Abstract: The study of transferability of simple sequence repeats (SSR) among closely related species is a well-known strategy in population genetics, however transferability among distinct genera is less common. We tested cross-genera SSR amplification in the family Cactaceae using a total of 20 heterologous primers previously developed for the genera Ariocarpus, Echinocactus, Polaskia and Pilosocereus, in four taxa of the genus Cereus: C. fernambucensis subsp. fernambucensis, C. fernambucensis subsp. sericifer, C. jam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
0
10
2
Order By: Relevance
“…In the present study, the transferability observed (9.05%) was similar to the average of approximately 10% reported in cross-genera transferability studies of eudicots between 1997 and mid-2006 ( Barbará et al, 2007 ). However, the percentage transferability determined here was lower than the cross-genera amplification percentage observed in some families, such as Bignoniaceae (40.58%) ( Kalia et al, 2020 ) and Cactaceae (35.16%) ( Bombonato et al, 2019 ), and much lower than that between species within the same genus ( Miranda et al, 2020 ; Pern et al, 2020 ; Li et al, 2021 ). The transferability of SSR markers between species or genera is determined by the conservation of DNA sequences and the stability of primer binding sites in flanking regions of SSRs during evolution ( Ellegren, 2000 ; Saeed et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 75%
“…In the present study, the transferability observed (9.05%) was similar to the average of approximately 10% reported in cross-genera transferability studies of eudicots between 1997 and mid-2006 ( Barbará et al, 2007 ). However, the percentage transferability determined here was lower than the cross-genera amplification percentage observed in some families, such as Bignoniaceae (40.58%) ( Kalia et al, 2020 ) and Cactaceae (35.16%) ( Bombonato et al, 2019 ), and much lower than that between species within the same genus ( Miranda et al, 2020 ; Pern et al, 2020 ; Li et al, 2021 ). The transferability of SSR markers between species or genera is determined by the conservation of DNA sequences and the stability of primer binding sites in flanking regions of SSRs during evolution ( Ellegren, 2000 ; Saeed et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 75%
“…SSR transferability across species and sub-genera has been demonstrated by earlier studies in several plant genera e.g. Pinus [ 36 ], Cereus [ 37 ], Betula [ 38 ], and Hibiscus [ 39 ]. With reference to the Poaceae family, cross-species transferability of SSRs has been shown in sugarcane [ 40 , 41 ], guinea grass [ 31 ], ryegrass [ 33 ], bamboo [ 42 ], and koronivia grass [ 43 ].…”
Section: Introductionmentioning
confidence: 88%
“…Moreover, the possibility of effectively transferring these markers across taxa may overcome the challenges, cost, and time-consuming development of new SSR primers [ 53 , 55 ]. In cacti, this technique has been applied with success ( Table S1 ) at both the cross-species and cross-genera levels [ 28 , 56 , 57 , 58 , 59 , 60 ]. In addition to the possibility of cross-amplification using heterologous primers, the emergence of NGS technologies has allowed the description of new SSR loci from bioinformatic surveys (e.g., [ 51 , 61 ]).…”
Section: Discussionmentioning
confidence: 99%